VerdeScale a green port approach in the mixed-use redevelopment of Navotas Fish Port Complex - Dayco, Athea C.
In the Philippines, the Navotas Fish Port Complex (NFPC) is the center of the seafood industry, supplying fishery products in Metro Manila and other nearby provinces. Years of unregulated growth and no proper planning led to the port’s inability to meet growing fish demands and caused post-harvest losses. This study proposes a redevelopment of the Navotas Fish Port Complex using a green port approach and mixed-use development strategy, adapting it to modern sustainable standards provided by green port key factors and sustainable development goals. Together with the work domain inside the complex, the design also envisions different spaces that accommodate various recreational, commercial, historical, and cultural activities that harmonize social, economic, and environmental elements. Through user analysis and thematic+spatial analysis, and data collection methods such as interviews, the walk-and-talk method, and surveys, the study identified several critical issues: the absence of proper utility plans, intense competition for limited space, lack of green spaces, and the users' attachment to the area as both their home and workplace. These findings highlight the urgent need for a comprehensive redevelopment plan. The conclusion drawn from the analysis is that implementing the proposed redevelopment design will transform the Navotas Fish Port Complex into a Green Mixed-use Fish Port Complex. This transformation will not only address the existing issues but also enhance the port's capacity to meet future demands sustainably, supporting the economic and environmental sustainability of the region.